Further studies on Scirtothrips genus-group (Thysanoptera, Thripidae) in Japan, with five new species - Masumoto, Masami; Okajima, Shûji (Zootaxa, 2019)
Previously four genera and eight species of Scirtothrips genus-group have been known from Japan. Five new species are described, Scirtothrips betulaceae sp. n., S. cryptomeriae sp. n., S. illicii sp. n., S. passiflorae sp. n. and S. pini sp. n., and Anascirtothrips arorai is newly recorded from Japan. Moreover, males of Parascirtothrips fagaceae and S. flavus are described for the first time.